Ferroelectric device of hafnium oxide-based thin film based on interface engineering and preparation method of ferroelectric device

By controlling the TiO2 termination layer on the strontium niobium titanate substrate, a strontium doped hafnium oxide film was prepared, which solved the problem of ferroelectric performance instability caused by the polycrystalline structure of hafnium ferroelectric devices, and achieved high stability and iron of the HSO film Improved electrical performance.

CN119451566APending Publication Date: 2025-02-14HEBEI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411383185.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing hafnium oxide ferroelectric devices are prone to instability in ferroelectric properties due to polycrystalline structure, and there are problems of wake-up effect and low durability.

Method used

By accurately controlling the TiO2 termination layer on the strontium niobium titanate substrate, a strontium doped hafnium oxide film is prepared to achieve high stability of the ferroelectric orthogonal phase of the HSO film.

Benefits of technology

The ferroelectricity of the HSO film is significantly improved, ensuring the stability of the ferroelectricity in the HSO film as thin as 5nm, avoiding the wake-up effect, and improving the performance and durability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451566A_ABST
    Figure CN119451566A_ABST
Patent Text Reader

Abstract

The invention provides a ferroelectric device of a hafnium oxide-based thin film based on interface engineering and a preparation method of the ferroelectric device. The structure of the ferroelectric device comprises a substrate, a strontium-doped hafnium oxide film located on the substrate and a top electrode located on the strontium-doped hafnium oxide film. The substrate is a niobium strontium titanate substrate, and an interface, connected with the strontium-doped hafnium oxide thin film, on the niobium strontium titanate substrate is a TiO2 stop layer. According to the method, the interface terminal (TiO2 terminal or SrO terminal) of the niobium strontium titanate substrate (NSTO) is accurately controlled, and the strontium-doped hafnium oxide film (HSO) is prepared at the TiO2 terminal, so that the high stability of the ferroelectric orthogonal phase of the HSO film is realized. Compared with the SrO terminal, the HSO interface of the TiO2 terminal can more effectively enhance the ferroelectricity in the HSO thin film, and the stable ferroelectricity can be realized even in the HSO thin film with the thickness of 5nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferroelectric devices, in particular to a ferroelectric device of a hafnium oxide-based thin film based on interface engineering and a preparation method thereof. Background Art

[0002] Since the discovery of ferroelectricity in Si-doped HfO2 thin films in 2011, HfO2-based thin film materials have attracted widespread attention due to their strong ferroelectricity in low dimensions and compatibility with CMOS technology. HfO2 material itself has different crystal phases at high temperatures, such as cubic phase, tetragonal phase and monoclinic phase. However, none of these phases are ferroelectric phase structures. Numerous reports have confirmed that ferroelectricity is closely related to its low-symmetry orthorhombic phase (space group is Pbca21), which can be stabilized by technical means such as thin film growth control. In particular, strontium-doped hafnium oxide (5% Sr:HfO2, abbreviated as HSO) has become the focus of research because it exhibits the strongest ferroelectric properties among the reported doped hafnium oxides. In the past, most zirconium-doped hafnium oxides (Hf 0.5 Zr 0.5 The research on HZO (HZO) thin films focuses on polycrystalline films, but polycrystalline films usually contain non-ferroelectric phases, such as the main t-phase and m-phase, which inhibit their ferroelectric properties and blur the understanding of the ferroelectric physics nature.

[0003] The main problem faced by existing hafnium oxide ferroelectric devices is that they are easily affected by growth conditions, interface oxygen vacancies and domain wall motion during the deposition process, resulting in a polycrystalline structure and unstable performance, especially the wake-up effect and low durability. In addition, the ferroelectricity of hafnium oxide films is poor under thin thickness conditions. This is mainly due to the large amount of m phase contained in its crystal structure and the large number of defects at the phase boundaries, which leads to problems such as unstable performance and easy fatigue of the device, limiting its development in the complementary metal oxide semiconductor market. Summary of the invention

[0004] The purpose of the present invention is to provide a ferroelectric device of a hafnium oxide-based thin film based on interface engineering and a preparation method thereof, so as to solve the problem that the existing hafnium oxide ferroelectric device is prone to unstable ferroelectric performance due to polycrystalline.

[0005] The present invention is achieved in that:

[0006] A ferroelectric device of hafnium oxide-based thin film based on interface engineering comprises a substrate, a strontium-doped hafnium oxide thin film located on the substrate, and a top electrode located on the strontium-doped hafnium oxide thin film; the substrate is a strontium niobium titanate substrate, and the interface between the strontium niobium titanate substrate and the strontium-doped hafnium oxide thin film is a TiO2 termination layer.

[0007] Preferably, the strontium niobium titanate substrate is a strontium niobium titanate substrate with a (111) crystal plane.

[0008] Preferably, the strontium niobium titanate substrate is a 0.7% Nb:SrTiO3 substrate.

[0009] Preferably, the strontium-doped hafnium oxide film is a 5% Sr:HfO2 film.

[0010] Preferably, the strontium-doped hafnium oxide film has a thickness of 5 to 12 nm.

[0011] The method for preparing the above-mentioned hafnium oxide-based thin film ferroelectric device based on interface engineering comprises the following steps:

[0012] (1) using strontium niobium titanate as a substrate and using a hydrofluoric acid solution to corrode the strontium niobium titanate substrate;

[0013] (2) Preparation of strontium-doped hafnium oxide thin film: placing a strontium niobium titanate substrate in a vacuum chamber of a pulsed laser deposition system and heat treating it at 850°C for 1.5 hours to form a TiO2 termination layer on the termination end of the strontium niobium titanate substrate; then sputtering a strontium-doped hafnium oxide thin film on the TiO2 termination layer by a pulsed laser deposition process;

[0014] (3) The top electrode was prepared on the strontium-doped hafnium oxide film by magnetron sputtering process.

[0015] Preferably, in step (2), when the strontium-doped hafnium oxide thin film is sputtered and grown on the TiO2 termination layer by a pulsed laser deposition process, the pressure is controlled to be 7.5-75 mTorr.

[0016] Preferably, in step (1), the strontium niobium titanate substrate is corroded with a hydrofluoric acid solution, specifically, the strontium niobium titanate substrate is immersed in a diluted solution of deionized water and hydrofluoric acid in a volume ratio of 3:1 for 1 minute.

[0017] Preferably, after the strontium niobium titanate substrate is corroded with a hydrofluoric acid solution in step (1), ultrasonic cleaning is performed to remove surface stains, and then the strontium niobium titanate substrate is placed in an acetone solution for ultrasonic cleaning for 10 minutes, and then placed in an alcohol solution for ultrasonic cleaning for 10 minutes, and finally blown dry with high-purity nitrogen.

[0018] The present invention achieves high stability of the ferroelectric orthorhombic phase of the HSO film by precisely controlling the interface terminal (TiO2 terminal or SrO terminal) of the niobium strontium titanate substrate (NSTO) and preparing a strontium-doped hafnium oxide film (HSO) at the TiO2 terminal. Compared with the SrO terminal, the HSO interface of the TiO2 terminal can more effectively enhance the ferroelectricity in the HSO film, and can achieve stable ferroelectricity even in the HSO film as thin as 5nm.

[0019] The present invention regulates the different termination surfaces of the strontium niobium titanate substrate electrode through interface engineering, and stabilizes the ferroelectric phase structure of the HfO2-doped (5% Sr:HfO2-HSO) film to achieve high epitaxial growth. Hafnium oxide-based films have a wide range of applications in microelectronic memory, ferroelectric field effect transistors, and neuromorphic computing, and have shown important potential in the application of achieving stable ferroelectric orthorhombic phases. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a spherical aberration electron microscope image of the sample obtained in Example 1 of the present invention at a low magnification.

[0021] Figure 2 This is a spherical aberration electron microscope image of the sample obtained in Example 1 of the present invention at a high magnification.

[0022] Figure 3 This is an IV curve test diagram of the sample obtained in Example 1 of the present invention.

[0023] Figure 4 3 is the switching characteristic curve of the sample obtained in Example 1 of the present invention.

[0024] Figure 5 It is a comparison chart of XRD test results of samples obtained in Examples 1-4 of the present invention.

[0025] Figure 6 This is the XRD test result diagram of the sample obtained in Example 1 of the present invention.

[0026] Figure 7 This is the XRD test result diagram of the sample obtained in Example 5 of the present invention.

[0027] Figure 8 This is the XRD test result diagram of the sample obtained in Example 6 of the present invention.

[0028] Fig. 9 This is the XRD test result diagram of the sample obtained in Example 7 of the present invention. DETAILED DESCRIPTION

[0029] The ferroelectric device of hafnium oxide-based thin film based on interface engineering provided by the present invention uses strontium niobium titanate 0.7% Nb:SrTiO3 (abbreviated as NSTO) as substrate and bottom electrode, and prepares strontium-doped hafnium oxide (HSO) thin film under the TiO2 terminal structure by accurately controlling the terminal structure (TiO2 or SrO terminal, or termination layer) of the NSTO bottom electrode, which can significantly improve the crystallization quality of the ferroelectric orthorhombic phase of the HSO thin film, and can observe obvious ferroelectric phase in the HSO thin film as thin as 5nm without awakening effect.

[0030] The present invention regulates the ferroelectricity of the HSO film through interface engineering, and the technology enhances the ferroelectricity of the HSO film through interface charge transfer and hole doping. The present invention is described in detail below with reference to specific examples.

[0031] Example 1

[0032] This embodiment uses pulsed laser deposition technology to prepare hafnium oxide doped strontium ferroelectric devices. The following is a detailed preparation process:

[0033] (1) First, the 0.7% Nb: SrTiO3 substrate used is pretreated. The substrate selected in this embodiment is a NSTO substrate with a (111) crystal plane. Different process steps will eventually result in different structures of the interface termination layer, which will directly affect the ferroelectricity of the HSO film prepared later. The termination layer obtained in this embodiment is the substrate interface of TiO2.

[0034] In order to control the interface terminal, the NSTO substrate was first subjected to a buffered hydrofluoric acid etching treatment, specifically: the substrate was immersed in a 3:1 deionized water and hydrofluoric acid solution (40%, analytical grade) for 1 minute, and then ultrasonically cleaned to remove surface stains; then the substrate was placed in an acetone solution for ultrasonic cleaning for 10 minutes to remove organic pollutants on its surface, and then placed in an alcohol solution for ultrasonic cleaning for 10 minutes to wash off the acetone solvent remaining on it, and then taken out and blown dry with high-purity nitrogen for use.

[0035] Subsequently, the substrate was placed in a pulsed laser deposition vacuum chamber and heat treated at 850°C for 1.5 hours to obtain a TiO2 termination layer. This step was performed simultaneously with the growth of the HSO film and is therefore described in detail in the following step (2).

[0036] (2) Use quick-drying conductive silver glue to stick the substrate on the sample stage of the pulsed laser deposition system, and then put it into the loadlock (injection chamber), close the chamber door of the loadlock, and turn on the mechanical pump, the side pump valve, and the quartz gauge vacuum gauge to perform preliminary vacuum treatment. After the pressure of the vacuum chamber is reduced to below 37.5mTorr, the system will close the side pump valve and perform higher vacuum environment treatment. At this time, the front valve in the system will automatically open to ensure the normal exhaust of the molecular pump, and then start the molecular pump and check the working status of the water chiller. After it is correct, wait for the program to automatically evacuate the vacuum, turn on the ionization vacuum gauge and check whether the pressure drops normally, so that the cavity can be processed by the molecular pump for a faster high vacuum. After using a molecular pump to reduce the pressure of the vacuum chamber to 9E-8Torr, open the gate valve between the loadlock chamber and the main chamber (growth chamber / main chamber), and use a transfer rod to send the sample stage with the sample attached and the HSO target (the HSO target is a mixture of hafnium oxide and strontium in a molar ratio of 95:5, sintered in pure oxygen at 1600°C) into the main chamber. The sample is sent in and preparations are made for the formal temperature increase experiment.

[0037] Turn off the ionization vacuum gauge to prevent damage to the ionization vacuum gauge caused by the rapid change in pressure during the heating process. Turn on the heating module of the pulsed laser deposition system and lower the heating jacket. Control the heating rate before 700°C to 25°C per minute. After reaching 700°C, keep it for 30 minutes to allow the sample stage to be evenly heated. Then adjust the heating rate to 10°C per minute until 850°C, and keep it at 850°C for 1.5 hours (a TiO2 termination layer will be formed during this process). After the temperature stabilizes, introduce oxygen and turn on the excimer pulse laser for preheating. Close the sample baffle and adjust the laser light path to ensure that the laser is accurately irradiated on the corresponding HSO target. After the laser is charged, pre-sputter the HSO target to be deposited to remove surface impurities. The laser used is a KrF excimer laser with a wavelength of 248 (λ=248nm) and a laser energy density of 1.25J / cm 2 After 300 pulses of pre-sputtering, the system coordinated the adjustment of the gate valve angle and the oxygen flow rate (the system was automatically controlled, and only the target pressure needed to be input). In this embodiment, the pressure was controlled to be 53 mTorr, and the sample baffle was opened to formally grow HSO on the NSTO substrate with the TiO2 termination layer.

[0038] (3) In order to form a complete electrical device, the top electrode needs to be grown. After the Neocera pulsed laser deposition system has cooled down, the sample is taken out of the transfer rod and then taken out of the loadlock chamber. The loadlock is opened by inflating. The sample is taken out and placed on the sample stage of the vacuum chamber of the magnetron sputtering. The mask is fixed and pressed with high-temperature tape. After the pressure is reduced to 1.8E-7Torr, the DC source of the magnetron sputtering is turned on, and the argon bottle is opened to allow argon (25sccm) to enter the vacuum chamber. The throttle valve of the magnetron sputtering system is opened to control the argon environment to 7.5mTorr. The power of the DC source is set to 10W, the sample baffle is closed and the DC switch is turned on. Observe whether the argon in the chamber is ionized normally and bombards the Pd target to produce a glow discharge phenomenon. After the glow on the metal Pd target is stable, the baffle is opened for formal material growth. The Pd material will pass through the holes on the mask and be deposited on the top of the sample, forming a complete and usable electrical test structure. The growth time of the Pd electrode was controlled at 12 min. After 10 min of deposition, the magnetron sputtering system was turned off and the mask and sample were taken out.

[0039] The samples were tested by transmission electron microscopy, and the results were as follows: Figure 1 As shown in the figure, a 12nm thick 5% Sr:HfO2 film is grown on a 0.7% Nb:SrTiO3 substrate, and a 9nm thick Pd electrode is grown on a 5% Sr:HfO2 film. The TiO2 termination layer on the 0.7% Nb:SrTiO3 substrate is not shown in the figure because the TiO2 termination layer is atomically thick and cannot be displayed in a low-magnification spherical aberration electron microscope. Figure 2 The spherical aberration can be displayed in the electron microscope under high magnification. Figure 2 The lattice arrangement can be clearly observed, and there is no polycrystalline region in the sample.

[0040] The IV curve test of the sample obtained in this embodiment is as follows Figure 3 shown. Figure 3 It was demonstrated that the HSO ferroelectric device exhibited ultra-stable electrical properties, and the performance of the sample remained stable after 100 cycles with almost no jitter.

[0041] The switching characteristics of the samples obtained in this embodiment were tested, and the results are as follows: Figure 4 shown. Figure 4 The sample has a fast response characteristic under low voltage working environment, and the time required for a single trigger is 26ns, which is much lower than that of traditional materials. This will also greatly reduce power consumption. The low power consumption during ferroelectric switching is also very suitable for high-efficiency storage devices and low-power electronic devices.

[0042] The TiO2 surface NSTO (111)-HSO ferroelectric device prepared in this embodiment controls the growth of the ferroelectric metastable phase through interface engineering and the corresponding (111) crystal plane, and forms a highly epitaxial hafnium oxide doped strontium film through Neocera pulsed laser deposition, thereby overcoming the problem that the hafnium oxide ferroelectric metastable phase is difficult to grow, achieving the single crystal growth of hafnium oxide doped strontium, and improving the performance of the ferroelectric device.

[0043] Example 2

[0044] Compared with Example 1, in this example, the pressure is controlled to be 75 mTorr when growing HSO in step (2), and the other steps are the same as those in Example 1.

[0045] Example 3

[0046] Compared with Example 1, in this example, the pressure is controlled to be 7.5 mTorr when growing HSO in step (2), and the other steps are the same as those in Example 1.

[0047] Example 4

[0048] Compared with Example 1, in this example, the pressure is controlled to be 150 mTorr when growing HSO in step (2), and the other steps are the same as those in Example 1.

[0049] The samples in Examples 1-4 were subjected to XRD testing, and the results were as follows: Figure 5 As shown. Figure 5 The detailed image at 30° on the middle right shows that the peak is optimal when the pressure is 53mTorr, with the highest peak value and the shortest half-height width under the same pulses.

[0050] Example 5

[0051] Compared with Example 1, in this example, the 0.7% Nb:SrTiO3 substrate is changed to a substrate with a (110) crystal plane, and the other steps are the same as those in Example 1.

[0052] Example 6

[0053] Compared with Example 1, in this example, the 0.7% Nb:SrTiO3 substrate is changed to a substrate with a (100) crystal plane, and the other steps are the same as those in Example 1.

[0054] XRD tests were performed on the samples in Example 1, Example 5 and Example 6, and the results were as follows: Figure 6 , Figure 7 and Figure 8 As shown. Figure 6-Figure 8It can be seen that the hafnium oxide film on the (111)-TiO2 surface NSTO substrate has only (111) crystal orientation, while the (110) crystal surface NSTO has m-phase, and the (100) crystal surface NSTO has o-phase with very poor crystallinity, which are very unfavorable to ferroelectricity.

[0055] The present invention uses 0.7% Nb:SrTiO3 with different crystal planes directly as the substrate and bottom electrode, attempts to match the lattice of the ferroelectric orthorhombic phase with different crystal planes, and utilizes mechanisms such as interface reconstruction and domain matching epitaxy to obtain a better HSO ferroelectric orthorhombic phase. Finally, the atomic arrangement of the ferroelectric phase (such as Figure 2 ), confirming the epitaxial growth of the ferroelectric metastable phase.

[0056] Example 7

[0057] Compared with Example 1, this example obtains a substrate interface with a termination layer of SrO.

[0058] (1) First, the 0.7% Nb:SrTiO3 substrate used is pretreated. The substrate selected in this embodiment is a NSTO substrate with a (111) crystal plane. The NSTO substrate is subjected to a buffered hydrofluoric acid etching treatment, specifically: the substrate is immersed in a 3:1 deionized water and hydrofluoric acid solution for 1 minute, and then ultrasonically cleaned to remove surface stains; then the substrate is placed in an acetone solution for ultrasonic cleaning for 10 minutes to remove organic pollutants on its surface, and then placed in an alcohol solution for ultrasonic cleaning for 10 minutes to wash off the acetone solvent remaining on it, and then taken out and blown dry with high-purity nitrogen for use.

[0059] (2) A SrRuO3 (abbreviated as SRO) layer of one unit cell is grown on a pretreated 0.7% Nb:SrTiO3 substrate.

[0060] The SRO single crystal cell layer is grown by magnetron sputtering technology: First, the NSTO substrate is glued to the heated sample table of the magnetron sputtering with quick-drying conductive silver glue. When pasting the substrate, attention should be paid to the uniformity of the colloid. Too much will cause the colloid to overflow and contaminate the sample, and too little will easily lead to a decrease in the heat conduction effect, resulting in uneven heating. After the sample is glued and dried at a low temperature (120°C) on a special heating table, it is placed in the magnetron sputtering vacuum chamber. After placing it, close the sealed door of the sample chamber, turn on the mechanical pump switch, and slowly open the side valve for rough vacuum treatment. After the pressure in the chamber drops below 37.5mTorr (observed by the resistance gauge), close the side valve and prepare for high vacuum treatment. Turn on the power of the molecular pump, then open the fore valve to connect the molecular pump to the mechanical pump. Before turning it on, be sure to ensure that the pressure is not higher than 150mTorr to prevent the molecular pump from damaging the fan blades due to excessive pressure. Start the molecular pump and wait for the speed to increase to about 100Hz, then open the gate valve to connect the molecular pump to the chamber and perform high vacuum treatment on the chamber. After the molecular pump reaches full speed, open the ionization gauge and observe its reading until the pressure reaches 0.00375mTorr. After meeting the requirements, adjust the gate valve to a smaller angle state, flush 70sccm of argon and 25sccm of oxygen into the chamber, and adjust the angle of the gate valve to stabilize the pressure in the chamber at 22.5mTorr. Adjust the temperature program to rise to the required temperature (700℃) at a rate of 20℃ / min. In order to remove contaminants on the surface of the target, pre-sputter for 10min before formally growing the SRO film. At this time, it is necessary to close the baffle and turn on the RF power supply (power is 50W). After pre-sputtering, open the baffle for formal sputtering, and deposit a total of 20s, with a thickness of about the thickness of a single cell. At the end of the growth, the gate valve is completely closed, the molecular pump switch is turned off to reduce the speed, and 0.8 atmospheres of high-purity oxygen is filled into the cavity to reduce the generation of oxygen defects. The cooling rate is adjusted to 5°C / min, and the formal in-situ annealing and cooling begins to complete the growth of the SRO single crystal cell.

[0061] The SRO thin layer is then kept in a PLD vacuum chamber at 850°C and an oxygen pressure of 10 mTorr for 30 minutes to volatilize the Ru element in the SRO single crystal layer, leaving a SrO termination layer composed of Sr and O. The SrO termination layer formed by the high-temperature volatilization of the Ru element is carried out simultaneously with the growth of the HSO thin film, which is described in detail in step (3).

[0062] (3) The substrate with the SRO thin layer is pasted on the sample stage of the pulsed laser deposition system with quick-drying conductive silver glue, and then placed in the loadlock. The chamber door of the loadlock is closed, and the mechanical pump, the side pump valve, and the quartz gauge vacuum gauge are turned on to perform preliminary vacuum treatment. After the pressure of the vacuum chamber is reduced to below 37.5mTorr, the system will close the side pump valve and perform higher vacuum environment treatment. At this time, the front valve in the system will automatically open to ensure the normal exhaust of the molecular pump, and then start the molecular pump and check the working status of the water chiller. After it is correct, wait for the program to automatically evacuate the vacuum, turn on the ionization vacuum gauge and check whether the pressure drops normally, so that the cavity can be processed by the molecular pump for a faster high vacuum. After using a molecular pump to reduce the pressure of the vacuum chamber to 9E-8Torr, open the gate valve between the loadlock chamber and the main chamber (growth chamber / main chamber), and use a transfer rod to send the sample stage with the sample attached and the HSO target (the HSO target is a mixture of hafnium oxide and strontium in a molar ratio of 95:5, sintered in pure oxygen at 1600°C) into the main chamber. The sample is sent in and preparations are made for the formal temperature increase experiment.

[0063] Turn off the ionization vacuum gauge to prevent damage to the ionization vacuum gauge caused by the rapid change in pressure during the heating process. Turn on the heating module of the pulsed laser deposition system and lower the heating jacket. Control the heating rate before 700°C to 25°C per minute. After reaching 700°C, keep it for 30 minutes to allow the sample stage to be evenly heated. Then adjust the heating rate to 10°C per minute until 850°C. Pass oxygen at a pressure of 10mTorr and keep it for 30 minutes to volatilize the Ru element and form an SrO termination layer. After the temperature stabilizes, pass oxygen and turn on the excimer pulse laser for preheating. Close the sample baffle and adjust the laser optical path to ensure that the laser is accurately irradiated on the corresponding HSO target. After the laser is charged, pre-sputter the HSO target to be deposited to remove surface impurities. The laser used is a KrF excimer laser with a wavelength of 248 (λ=248nm) and a laser energy density of 1.25J / cm 2 After 300 pulses of pre-sputtering, the system coordinated the adjustment of the gate valve angle and the oxygen flow rate (the system was automatically controlled, and only the target pressure needed to be input). In this embodiment, the pressure was controlled to be 53 mTorr, and the sample stage baffle was opened to formally grow HSO on the NSTO substrate with the SrO termination layer.

[0064] (4) This step is the same as step (3) in Example 1, and a Pd electrode is grown on the HSO film layer.

[0065] The samples obtained in this example were subjected to XRD test, and the results were as follows: Fig. 9 As shown. Figure 6 and Fig. 9It can be seen that the ferroelectric orthorhombic phase peak of the SrO surface is significantly weakened compared with the TiO2 surface under the same number of deposition pulses, and the half-height width is increased, which highlights the advantage of the TiO2 surface in growing the hafnium oxide ferroelectric orthorhombic phase.

[0066] The present invention effectively improves the growth probability of the hafnium oxide metastable phase, controls its growth structure through different interfaces, achieves highly epitaxial single crystal ferroelectric phase growth, and provides a technical basis for further improving the performance of ferroelectric devices.

Claims

1. A ferroelectric device of hafnium oxide-based thin film based on interface engineering, characterized in that: It comprises a substrate, a strontium-doped hafnium oxide film on the substrate and a top electrode on the strontium-doped hafnium oxide film; the substrate is a strontium niobium titanate substrate, and the interface between the strontium niobium titanate substrate and the strontium-doped hafnium oxide film is a TiO2 termination layer.

2. The ferroelectric device of hafnium oxide-based thin film based on interface engineering according to claim 1, characterized in that: The strontium niobium titanate substrate is a strontium niobium titanate substrate with a (111) crystal plane.

3. The ferroelectric device of hafnium oxide-based thin film based on interface engineering according to claim 2, characterized in that: The strontium niobium titanate substrate is a 0.7% Nb:SrTiO3 substrate.

4. The ferroelectric device of hafnium oxide-based thin film based on interface engineering according to claim 1, characterized in that: The strontium-doped hafnium oxide film is a 5% Sr:HfO2 film.

5. The ferroelectric device of hafnium oxide-based thin film based on interface engineering according to claim 1, characterized in that: The thickness of the strontium-doped hafnium oxide film is 5-12 nm.

6. A method for preparing a ferroelectric device of a hafnium oxide-based thin film based on interface engineering according to any one of claims 1 to 5, characterized in that: The steps include: (1) using strontium niobium titanate as a substrate and using a hydrofluoric acid solution to corrode the strontium niobium titanate substrate; (2) Preparation of strontium-doped hafnium oxide thin film: placing a strontium niobium titanate substrate in a vacuum chamber of a pulsed laser deposition system and heat treating it at 850°C for 1.5 hours to form a TiO2 termination layer on the termination end of the strontium niobium titanate substrate; then sputtering a strontium-doped hafnium oxide thin film on the TiO2 termination layer by a pulsed laser deposition process; (3) The top electrode was prepared on the strontium-doped hafnium oxide film by magnetron sputtering process.

7. The method for preparing a ferroelectric device of a hafnium oxide-based thin film based on interface engineering according to claim 6, characterized in that: In step (2), when the strontium-doped hafnium oxide thin film is sputtered and grown on the TiO2 termination layer by a pulsed laser deposition process, the pressure is controlled to be 7.5 to 75 mTorr.

8. The method for preparing a ferroelectric device of a hafnium oxide-based thin film based on interface engineering according to claim 6, characterized in that: In step (1), the strontium niobium titanate substrate is corroded by using a hydrofluoric acid solution, specifically, the strontium niobium titanate substrate is immersed in a deionized water and hydrofluoric acid solution with a volume ratio of 3:1 for 1 minute.

9. The method for preparing a ferroelectric device of a hafnium oxide-based thin film based on interface engineering according to claim 8, characterized in that: In step (1), after the strontium niobium titanate substrate is corroded by a hydrofluoric acid solution, ultrasonic cleaning is performed to remove surface stains, and then the strontium niobium titanate substrate is ultrasonically cleaned in an acetone solution for 10 minutes, and then in an alcohol solution for ultrasonic cleaning for 10 minutes, and finally blown dry with high-purity nitrogen.